Perception on the Use of ICTs in the Teaching Practices of Special Education Teachers - Aburto Godoy, Raquel A. (2011)
This paper includes the results of a questionnaire on the perception and use of technological resources in the teaching practices developed by special education teachers who worked with differentiated groups in the community of Chillán, Chile, during 2009. This questionnaire was applied through the 2.0 Google Docs tool. The answers provided by the participant teachers were analyzed through statistical tests, with a descriptive design. The questionnaire applied was created and validated for this research; therefore, this research project provides an accurate, easy-to-apply tool for the scientific community.